A Business Intelligence Platform to Support Legal Data Management at the TJMA - Justino, Adrielson F.; S. Neto, Jonas C.; Rodrigues, Thyago M.; Santana, Ewaldo E. C.; J. Junior, Antonio F. L.; Lobato, Fabio M. F. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Courts worldwide face an increasing case backlog, making it essential to develop technological solutions that improve efficiency in case management. Problem: Despite advances in Information and Communication Technologies and the adoption of electronic case management systems, handling large volumes of procedural data remains challenging, particularly in managing case processes and recurring cases of similar legal matters. Solution: This paper explores how a Business Intelligence tool can support judicial precedent and suspended case management by offering filtering, grouping, and duplicate case identification functionalities, integrated with the Case Management Center System. IS Theory: This study is based on the Organizational Information Processing Theory, emphasizing the need to align information processing capabilities with organizational information demands to manage complex data effectively. Method: Using Design Science Research, a technological artifact was developed in collaboration between the Court of Justice of the State of Maranhão and the State University of Maranhão, with a case study focused on the specific challenges of managing legal precedents and suspended cases. Summary of Results: The tool effectively centralizes and interactively visualizes procedural data, optimizing time for identifying duplicate cases and providing a solid foundation for more informed judicial decisions. The artifact has been approved by the Maranhão State Court and is now publicly available on the court’s website, enhancing accessibility and transparency. Contributions and Impact in IS Field: The tool enhances administrative efficiency and judicial productivity at the Maranhão State Court. This work contributes to academia by addressing gaps in BI application for judicial management and offers a practical solution for data-intensive environments in the industry.